Terror and Horror : Gothic Crosscurrents in Literature - Bhandari, Sabindra Raj (Janapriya Journal of Interdisciplinary Studies, 2020)
The word “Gothic” was originally implied to anything that is wild, barbarous, destructive and outlandish. When applied to literature, the term, was used both with eulogistic and disparaging connotations and became the synonyms for the grotesque, ghastly and violently supernatural. The literature was based on gloom, fear, terror and horror. In its long run, the Gothic literature got its horizon expanded with the touch of novelty and multi dimensional perspectives. This study relates the affinity between the spirits of Gothic architecture and literature that came as a vogue in late eighteenth century England. The main argument of this study is to reveal how the spirits of horror and terror intersected in literature. Similarly, it is also interesting to see how the aspects of horror and terror have crosscurrents between themselves. The more the genre found its way, there remained crosscurrents between the Gothic literatures propagated in Germany, England and France. This study is qualitative and its nature, purpose and approaches are historical. As such, this study makes a systematic and objective evaluation of facts, themes and ideas related to the previous study to understand causes, development, and trends of Gothic. This analysis helps to explain the present relevance, and also anticipates future aspects of the Gothic literature, exploring how this literature got its efflorescence in our own day being modern Gothic, which incorporates many shades of interpretations.